The Economic Activity of The Khazar Kingdom During the First Abbasid Era: (132-232A.H/749-847A.D) - AlKhalidi, Ragheed Gumar Majeed (Al-Adab Journal, 2021)
The Arab Islamic State witnessed During the first Abbasid era a great economic activity, including commercial activity. The commercial caravans coming from the East and the West arrived in Baghdad, the capital of the Abbasid state, loaded with various types of goods that were popular with people, and from the relations with which the Abbasid state had ties with the Kingdom of the Khazars, and they From one of the Turk tribes, who were pagan before their conversion to Judaism by embracing the Khazars of this religion, the relations between the Abbasid state and the Kingdom of the Khazars were characterized by attraction and conflicts, and these faltering relations are not new, but go back to the eras of the Rashidun and Umayyad Caliphates. It was ambiguous, and the historical sources did not directly mention the existence of industrial activity in this kingdom, and references to agricultural activity were very limited. The commercial sector occupied the largest place in the historical sources’ references to the arrival of commercial caravans from the neighboring provinces to the city of Atl, the capital of the Khazar Kingdom, and the settlement of a portion of Muslim merchants there, as well as the references to the markets in them, and references to the tithe tax that the Khakan Khazar imposed on these commercial caravans. Pass within the borders of his kingdom.